2018
DOI: 10.1021/acsaem.8b00705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoroethylene Carbonate Electrolytes on the Nanostructure of the Solid Electrolyte Interphase and Performance of Lithium Metal Anodes

Abstract: The mechanism for the performance enhancement of lithium metal electrodes by fluoroethylene carbonate (FEC) is revealed. Electrolytes containing FEC, 1.2 M LiPF6 in ethylene carbonate (EC):ethyl methyl carbonate (EMC) (3:7, vol) with 10% FEC (mass %) and 1.2 M LiPF6 in FEC, improve the electrochemical performance of both Li∥Li and Cu∥LiFePO4 cells compared to the baseline electrolyte, 1.2 M LiPF6 in EC:EMC (3:7, vol). Ex situ surface analysis of lithium metal electrodes after the initial plating demonstrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 36 publications
13
118
0
Order By: Relevance
“…We suggest that the addition of FEC resulted in mainly fluorinated‐rich SEI with LiF, and trapped LiTFSI . This is because the C 1s XPS spectrum is dominated by carbon‐fluorine bonds at 291.8 eV (LiTFSI, C‐F x ) and at 287.1 eV assigned to C−CF x .…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…We suggest that the addition of FEC resulted in mainly fluorinated‐rich SEI with LiF, and trapped LiTFSI . This is because the C 1s XPS spectrum is dominated by carbon‐fluorine bonds at 291.8 eV (LiTFSI, C‐F x ) and at 287.1 eV assigned to C−CF x .…”
Section: Resultsmentioning
confidence: 88%
“…It was suggested that LiF nanoparticles precipitate on the electrode‘s surface under a certain diameter an ultra‐microelectrode‐like surface termination may form. In turn, this termination leads to a uniform diffusion field giving rise to more uniform stripping and plating of lithium on copper current collectors . In addition, we suggest that the presence of fluorine throughout the SEI may indicate that some of the FEC reduction products encapsulate residual lithium anion salt (TFSI).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations